Structure of Dung Beetle Communities in an Altitudinal Gradient of Neotropical Dry Forest - Marin Armijos, D. (2015)
To understand the effects of global warming in tropical insect communities, it is necessary to comprehend how such communities respond to different abiotic factors that covariate with altitude. In this study, we partially answer this question applied to dung beetle communities distributed along an altitudinal gradient. The sampling was conducted in seven stations 100 m apart each in altitude in a dry mountain scrub in southern Ecuador. A total of 7422 individuals belonging to six species were captured. Canthon balteatus Boheman was the most abundant with 6502 individuals, and Onoreidium ohausi (Arrow) was the least abundant with 20 individuals. We found significant changes in the structure of the dung beetle communities with altitude. Two abiotic factors showed a relationship with the abundance pattern for all species (altitude, Z = 0.011, p < 0.01, and temperature, Z = 0.859, p < 0.01). Canthon balteatus Boheman showed a positive relationship with altitude (Z = 1.422, p < 0.001) and temperature (Z = 1.121, p < 0.001), Dichotomius problematicus (Lederwaldt) a positive relationship with precipitation (Z = 0.113, p < 0.001), and Malagoniella cupreicollis (Waterhouse) a positive relationship with temperature (Z = 0.668, p < 0.001) and negative with precipitation (Z = ?0.189, p < 0.001). Phanaeus achilles Boheman, Onthophagus sp., and O. ohausi (Arrow) did not show any relationship with the studied variables, nor was the richness correlated with the studied variables. These results suggest that the effects of global warming over dung beetle communities will be difficult to predict because of species-specific responses to global warming. © 2014, Sociedade Entomológica do Brasil.